Telehealth delivery of adapted CBT-I for insomnia in chronic pain patients: a single arm feasibility study - Zambelli, Zoe; Halstead, Elizabeth J.; Fidalgo, Antonio R.; Mangar, Stephen; Dimitriou, Dagmara (Frontiers in Psychology, 2024)
A large proportion of individuals with chronic pain experience insomnia-related symptoms which can be persistent in nature, and negatively impact one's quality of life. This single arm trial aimed to investigate the feasibility and preliminary efficacy of CBT-I, adapted for people with chronic musculoskeletal pain, delivered via telehealth.We conducted a single arm feasibility trial in which 10 adult women (M age = 50.76 years, SD = 8.03 years) with self-reported insomnia and a diagnosed chronic musculoskeletal chronic pain received six CBT-I individual treatment sessions over six to ten weeks. Treatment was delivered via telehealth. Participants completed weekly sleep diaries, and self-reported measures of insomnia, pain, anxiety and depression pre-treatment, post-treatment, and one-month follow-up.The trial yielded, high levels of compliance with intervention protocols, and affirmative feedback on satisfaction which demonstrated feasibility. The enrolment rate into the study was 37% (27 participants screened, ten participants enrolled).The intervention was associated with statistically and clinically meaningful improvements in self-reported insomnia severity. There were statistically significant improvements in sleep efficiency, wake after sleep onset, sleep onset latency, anxiety and depression.Adapted CBT-I delivered via telehealth may be a feasible, acceptable, and efficacious therapeutic approach for individuals with co-existent sleep and chronic pain. Future trials should adopt a randomised design against usual care.